Relationship between illness uncertainty, anxiety, fear of progression and quality of life in men with favourable‐risk prostate cancer undergoing active surveillance. (21st April 2015) - Parker, Patricia A.; Davis, John W.; Latini, David M.; Baum, George; Wang, Xuemei; Ward, John F.; Kuban, Deborah; Frank, Steven J.; Lee, Andrew K.; Logothetis, Christopher J.; Kim, Jeri
Abstract : Objectives: To evaluate prospectively the associations between illness uncertainty, anxiety, fear of progression and general and disease‐specific quality of life (QoL) in men with favourable‐risk prostate cancer undergoing active surveillance (AS). Patients and Methods: After meeting stringent enrollment criteria for an AS cohort study at a single tertiary care cancer centre, 180 men with favourable‐risk prostate cancer completed questionnaires at the time of enrollment and every 6 months for up to 30 months. Questionnaires assessed illness uncertainty, anxiety, prostate‐specific QoL (using the Expanded Prostate Cancer Index Composite [EPIC] scale) and general QoL (using the 12‐time short‐form health survey [SF‐12]) and fear of progression. We used linear mixed‐model analyses and multilevel mediation analyses. Results: Sexual scores on the EPIC scale significantly declined over time ( P < 0.05). Illness uncertainty was a significant predictor of all EPIC summary scores, SF‐12 physical component summary (PCS) scores, mental component summary (MCS) scores and fear of progression scores (all P < 0.05), after controlling for demographic and clinicopathological factors. Anxiety predicted all EPIC summary, MCS and fear of progression scores (all P < 0.05) but not PCS scores ( P = 0.08). Scores on PCS, MCS, EPIC summary scales (except sexual scale), and fear of progression did not change significantly over the study period (all P > 0.10). Conclusion: Over the 2.5‐year follow‐up, QoL remained stable; only sexual function scores significantly declined. Illness uncertainty and anxiety were significant predictors of general and prostate‐specific QoL and fear of progression. Interventions to reduce uncertainty and anxiety may enhance QoL for men with prostate cancer on AS.